2019
DOI: 10.1016/j.toxrep.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and potential sources of heavy metal contamination in fish species in River Ganga basin: Possible human health risks evaluation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
6
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 261 publications
(132 citation statements)
references
References 47 publications
11
93
6
3
Order By: Relevance
“…The daily intake of PTEs (μg/d bw) through the consumption of fish (8.219 g/d bw) was determined using Eq. 2 [17]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The daily intake of PTEs (μg/d bw) through the consumption of fish (8.219 g/d bw) was determined using Eq. 2 [17]:…”
Section: Resultsmentioning
confidence: 99%
“…However, arsenic could have originated from a different sources from the other PTEs. Some sources of the PTEs include agricultural runoff [17], upstream mine tailings dams [2] and animal feeds and manure from the piggeries [47]. One study reported high concentrations of PTEs in pig manure and feed [48].…”
Section: Temperature Ph and Organic Matter And Associations With Ptesmentioning
confidence: 99%
See 1 more Smart Citation
“…An unexpected, insufficient availability of insect's food can force fish species to migrate in search of food, where they might found the availability of greater revelation to predation. Similar to pesticides, herbicides can also trim down the reproductive success of fish species and other aquatic flora and fauna Maurya et al, 2016c;Maurya et al, 2019).…”
Section: Modification In Habitatmentioning
confidence: 99%
“…Some practices have caused environmental degradation. Community perception regarding the farmed Pradip Kumar Maurya et al (2019) fish species is that they are "cleaner" comparable to the wild fish species. On the other hand, various farmed fish have a much higher body burden of natural as well as man-made toxic production, e.g., in the form of antibiotics, insecticides, and pushy organic pollutants, than wild fish species.…”
Section: Introductionmentioning
confidence: 99%